Potential of transgenic crops in Bangladesh: findings from a consultation of Bangladeshi scientific experts - Gruère, Guillaume P. P.; Hoque, Imdadul; Valmonte-Santos, Rowena; Rosegrant, Mark W. (Springer, 2006)
This note summarizes the results of a consultation of scientific and regulatory experts in July 2005 on the potential of transgenic crops in Bangladesh. We find that Bangladeshi experts are optimistic on the potential of agricultural biotechnology to respond to biotic and abiotic stresses in their country in the future. Public research is constrained by human capacities, infrastructure and capital investment, and transgenic crop development will require the active involvement of outside partners, such as international organizations or collaboration with private companies. We also find that social acceptance of genetic engineering is not considered a major issue, but could become one, and prompted experts to call for a wider awareness campaign on the technology.